ミズホ コウゲン ノ タイキ ヒョウメン セキセツ チュウ ノ カガク セイブン ノ キョドウ - 金森, 悟; カナモリ, サトル; 金森, 暢子; カナモリ, ノブコ; 渡辺, 興亜; ワタナベ, オキツグ; 西川, 雅高; ニシカワ, マサタカ; 神山, 幸吉; カミヤマ, コウキチ; 本山, 秀明; モトヤマ, ヒデアキ; et al. (1997)
P(論文) 南極昭和基地の大気エーロゾルを1988,1989,1990年の3年間にわたり連続観測した。エーロゾル粒子に含まれる化学成分の内, exSO_4^<2->, MSA, NH_4^+等の成分が夏に高く冬に低い季節変化をする事を明らかにした。またガス状のHCl, SO_2,HNO_2,HNO_3の季節変化を明らかにし, 非常に高濃度のHClガスが夏期に出現し, 他の成分もエーロゾルに近い濃度になる事を示した。みずほ高原内陸および海上の大気エーロゾルの粒径分布を明らかにした。exSO_4^<2->とMSAは共に0.35μmに極大粒径を持ち, ガス体から生じた2次粒子であると思われる。ほとんどの大気エーロゾルは海塩に比較して負のexCl^-を示し, Cl^-がNa^+に対して欠損していることが認められた。みずほ高原内の5点における積雪ピットの観測から, 化学成分の季節変化は内陸の観測点でδ^<18>O, Cl^-およびNa^+につき見いだされた。飛雪では, Cl^-, Na^+, exSO_4^<2->, NO_3^-, MSA等の成分が海側で高く, 内陸に向かって減少し, 更に内陸で反転上昇し, 内陸に別の供給源があることを示唆した。ほとんどの雪は正のexCl^-を示した。みずほ高原の大気エーロゾルと対応する雪の間には, 化学成分濃度の比例関係がほぼ認められ, 積雪は大気エーロゾル中の濃度を大まかに反映している。しかしexCl^-, Ca^<2+>, K^+などはこの関係を満足しない場合が多いので, 地表の大気エーロゾル以外に高層大気からの寄与も考慮する必要がある。 Atmospheric aerosols were studied at Syowa Station, Antarctica for 3 years from 1988 to 1990. Some chemical species, such as exSO_4^<2->, MSA and NH_4^+, showed an annual trend, high in summer and low in winter. The seasonal variations of gaseous HCl, SO_2,HNO_2,HNO_3 were also studied and the occurrence of very high HCl gas in summer and the comparable concentrations of others gases to those of aerosols were found. The size distribution of aerosol particles over inland area and marine water were measured. The particle radius at the concentration maximum of exSO_4^<2-> as well as MSA were found at 0.35μm, indicating secondary particles production from gases. In most case, atmospheric aerosols had negative exCl^- value showing Cl^- defect as compared to Na^+. From the observation at 5 snow pits on the Mizuho Plateau, apparent seasonal variations in δ^<18>O, Cl^- and Na^+ were found only at the 2 inland points. From the drifting snow studies, Cl^-, Na^+, exSO_4^<2->, NO_3^- and MSA showed the distribution of high in sea-side and low in inland and then re-increase in the inner area indicating supply from inland. Most snow samples showed positive exCl^- values. A rough linear relationship among concentrations in chemical species was found between atmospheric aerosols and ...